Meat! : A Transnational Analysis - Subramaniam, Banu, 1966-; Chatterjee, Sushmita, 1976- (Book collections on Project MUSE., 2021)
"This volume frames meat as politics and with differential meanings as it travels the world. The contributors study the many guises of meat, through scales, and across time and place, to examine with renewed impetus the volatile and power-saturated meanings of "meat." The contributors endeavor to draw attention towards power configurations on a transnational scale in order to inspire forms of action that are attentive to histories of colonialism, racism, ableism, and sexism that frame "meat." Through a study of chicken, fish, beef bans, milk, barbecue, fake meat, cows, human and animal sacrifice, cannibalism, ash, veganism, exotic meat, frozen meat, technologies of meat, and various other issues and in-flows; our conversations remain productively haunted by the selective malleability and rigidity of what constitutes "meat" as it travels the world and its varied ethical imports"--